Performance optimization of a Darrieus wind turbine with straight controlled blades - Grinchenko, V.T.; Каyan V. P. (Reports of the National Academy of Sciences of Ukraine, 2015)
The possibility of increasing the energy efficiency of a Darrieus wind turbine with straight blades is considered. The basic idea is, by controlling the orientation of the blades relative to the oncoming flow, to optimize the magnitude of torque on the rotor shaft. The numerical solution of the two-dimensional problem of aerodynamics allowed us to obtain basic data for developing a mechanism for adjusting the position of the blades. The possibility of a practical realization is confirmed by the extensive experimental studies on several wind turbine models. The wind turbine with controlled blades is self-starting at a rather low speed of wind. The energy efficiency of such turbine is one and a half time higher than that of a turbine with fixed blades.